2002
DOI: 10.1634/theoncologist.7-3-210
|View full text |Cite
|
Sign up to set email alerts
|

Unique Features of the Mode of Action of ET-743

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 22 publications
0
28
0
2
Order By: Relevance
“…In addition to the activity reported for trabectedin as a single agent, mechanistic (D'Incalci et al, 2002;Kanzaki et al, 2002) and preclinical (Takahashi et al, 2002;Meco et al, 2003) studies have noted evidence of in vitro and in vivo synergism of trabectedin in combination with anthracyclines, taxanes and platin salts in experimental models of several solid tumours, including breast cancer. Phase I combination studies have also reported feasibility and activity in resistant solid tumours when trabectedin is combined with anthracyclines (Gianni et al, 2003;Cohen et al, 2005), paclitaxel (Chu et al, 2004), platinum compounds (Sessa et al, 2004) or capecitabine (Holden et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the activity reported for trabectedin as a single agent, mechanistic (D'Incalci et al, 2002;Kanzaki et al, 2002) and preclinical (Takahashi et al, 2002;Meco et al, 2003) studies have noted evidence of in vitro and in vivo synergism of trabectedin in combination with anthracyclines, taxanes and platin salts in experimental models of several solid tumours, including breast cancer. Phase I combination studies have also reported feasibility and activity in resistant solid tumours when trabectedin is combined with anthracyclines (Gianni et al, 2003;Cohen et al, 2005), paclitaxel (Chu et al, 2004), platinum compounds (Sessa et al, 2004) or capecitabine (Holden et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…This rather unique mechanism can account for the unusual behavior of these mutant cells because defects in NER proteins, which are involved in the repair of DNA damage caused by many DNA-binding anticancer drugs (e.g., the nitrogen mustard mechlorethamine, cisplatin, or MMC; refs. 5, 6), typically lead to increased drug sensitivity (5,40,41) and not the reverse, as is the case for trabectedin.…”
Section: Discussionmentioning
confidence: 99%
“…Trabectedin (Yondelis) is a novel antitumor agent originally isolated from the Caribbean marine tunicate, Ecteinascidia turbinata, which was selected for clinical investigation due to its potent cytotoxic activity against a variety of tumor cell lines in vitro and human tumor xenografts in vivo (1). Currently, trabectedin is undergoing phase II/III clinical trials both in Europe and the U.S., with promising results for the treatment of soft tissue sarcomas, and breast and ovarian cancers (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%